Factors Associated with Student Engagement in Online Learning During COVID-19 Pandemic: A Systematic Review - Limbu, Yam (Online Learning, 2025)
While prior studies have examined various determinants of student engagement in online learning during the COVID-19 pandemic, the findings are inconsistent. Thus, there is a need for a systematic review of the factors influencing student engagement in virtual learning during the pandemic that will provide state-of-the-art knowledge of existing literature in the domain and offer future research directions. This study systematically reviews factors driving college student engagement in online learning during the COVID-19 pandemic. This review was performed in accordance with the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses. A systematic search of four databases identified 32 eligible studies. The most prevalent factors influencing student engagement during the COVID-19 pandemic were student-related factors (e.g., student self-efficacy, emotion, motivation, personality, student-student interaction, and self-care practices). This was followed by instructor-related factors (e.g., self-efficacy, technical readiness, instructor-student interaction, teaching presence, and organization), course material and design-related factors (e.g., pedagogical approach, learning format, and learning activities), learning technology and system-related factors (e.g., learning technology and tools and perceived usefulness), and demographics (e.g., gender, college year, and ethnicity). These results provide a guide for future educational initiatives aimed at maximizing student engagement in an increasingly digital learning landscape, especially during exceptional times such as the pandemic. In particular, university resources should be directed at ensuring a smooth transition from face-to-face classroom experiences to emergency remote learning. This should include insights from students on which online practices foster the greatest engagement, motivation, and learning.